Volcanic facies and hydrothermal processes in Triassic pillow basalts from the Darno Unit, NE Hungary - Kiss, Gabriella, geologinja (Array, 2008)
Summary: The Darnó Unit within the Zagorje-Mid-Transdanubian Megaunit is an allochtonous part of Dinarides in NE-Hungary and represents a relict of the Neotethyan accretionary complex. It contains blocks of submarine basalts of Triassic age in turbiditic sediments olistrostrome of Jurassic age. The lava clogged in the lime mud at the original site of volcanism and developed closely packed pillow, pillow fragment hyaloclastite breccia, and peperite facies. Interaction between the lava and the sea water produced mostly chloritic alteration of basalt and precipitation of hydrothermal calcite in amygdales, feeding channels of lava lobes and hyaloclastite breccia cements. Calcite is associated with chlorite, epidote, hematite and pyrite. Fluid inclusions in calcite infillings record conditions of fluid/rock interaction. Salinities of fluid inclusions (3.2–5.6 wt.% NaCl equiv. wt.%.) are close to the salinity of recent sea water and their homogenization temperatures are in the range of 80–150°C. Fluid inclusion data support interpretation that volcanic facies represent rapidly cooled distal zones away from the submarine volcanic centre. This is also confirmed by the comparison to the volcanic and hydrothermal alteration facies of the submarine basalt lava-flow complex and associated pillow lava formation of Triassic age in the Hruškovec quarry in the Kalnik Mts., NW-Croatia. The obtained data contribute to understanding of the early history of Neotethyan evolution, i.e. dilemma about rifting or oceanization in Triassic time and offer new aspects of correlation between units of Dinaridic origin which had been displaced from their original setting by large scale Tertiary tectonic processes.